The nicest English is in Indiana - Preston, Dennis R (Studia Germanica Posnaniensia, 2018)
Nonlinguists' hand-drawn maps of their perceptions of US dialect areas reveal that prescription is an important part of their area identifications. Labels in these maps, however, indicate that two preferences may be at work - a preference for a "correct" English and another for a "pleasant" or "normal" variety. The fifty states, New York City, and Washington, D. C. were ranked for "pleasantness" of speech by young, white, well-educated, male and female residents of southern Indiana. The intensity of agreement (through standard deviations), a number of individual areas, the difference between men's and women's ratings, and the differences between the two modes of presentation of the research instrument are analyzed. The results are contrasted with an earlier ranking of the same areas by similar informants for the notion "correct" and generalized by being placed on a map representing the perception of US speech areas obtained from similar informants.